PEMAKAIAN KONTRASEPSI SUNTIK AKAN MEMPENGARUHI BERAT BADAN AKSEPTOR KB SUNTIK DI KOTA BARU DRIYOREJO - Kamariyah, Nurul (Universitas Nahdlatul Ulama Surabaya, 2014)
Acceptor use of contraceptive injection most complain weight increased. Although knowing acceptor increased weight, they keep use contraceptive injectable. Therefore, this study was purposed to find out the correlation between the use of contraceptive injection and the body weight change happening to the acceptors. The design of study was analytic-cross sectional. The population involved all  acceptors using  contraceptive  injection  for more  than  one  year,totally  89 people. 74 respondents were chosen as the samples by using probability sampling in  which  the  simple  random  sampling  technique  was  applied  in  this  study. Variable of this research are independent (the use of contraceptive injection) and dependent (the body weight change). The data were collected by using family planning registration card, observation sheets, and a weight scale. The data were processed by editing, coding and tabulating. The data analysis was done by using Mann-Whitney?s test with the significance level ? = 0.05.  The result of analysis showed that p = 0.007 < ? = 0.05 which meant that H0 was rejected most of the acceptors having three-month contraceptive injection had weight gain. describing that there was a  correlation between  the use of contraceptive injection and the body weight change happening to the acceptors. The conclusion of this study was that the use of contraceptive injection containing  hormone  affect  the  change  of  body  weight.  Thus,  the  correct counseling, information, and education to the acceptors contraceptive injection to choice non hormonal contraceptive if experienced excessive weight gain.